2017
DOI: 10.1177/0896920517740616
|View full text |Cite
|
Sign up to set email alerts
|

Reproducing Dystopia: The Politics of Transnational Surrogacy in India, 2002–2015

Abstract: In the decade following legalization of commercial surrogacy in 2002, India became the largest provider of surrogacy services. Then, in December 2015 commercial surrogacy was banned. In this article I show that commercial surrogacy was no panacea for working-class women, but the ban can potentially be far worse because the Indian state now allows only altruistic surrogacy between citizen couples and their women kinfolk who will provide gestation services for no monetary compensation. By positing altruistic sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…Literature from the Indian context on the psychosocial outcomes of surrogacy practice mainly exists in the form of cross-sectional studies, qualitative investigations, case-series, commentaries, review-articles primarily been conducted by Sociologists, Anthropologists and Public health experts. [ 31 32 33 34 35 36 37 38 39 40 41 42 43 ] Evidences in the form of clinical investigations, randomized controlled trials, systematic and meta-analytical studies are scarce.…”
Section: T He E Motional E mentioning
confidence: 99%
“…Literature from the Indian context on the psychosocial outcomes of surrogacy practice mainly exists in the form of cross-sectional studies, qualitative investigations, case-series, commentaries, review-articles primarily been conducted by Sociologists, Anthropologists and Public health experts. [ 31 32 33 34 35 36 37 38 39 40 41 42 43 ] Evidences in the form of clinical investigations, randomized controlled trials, systematic and meta-analytical studies are scarce.…”
Section: T He E Motional E mentioning
confidence: 99%
“…Whilst much scholarly attention has been devoted to commercial surrogacy, the presence of altruistic surrogacy models in countries such as the UK, Canada, Australia and New Zealand, and recently also India, may be seen as disturbing the commodification argument against surrogacy as the child emerges not as a commodity but as a gift. The preference for altruistic surrogacy has, however, been problematized by scholars who have pointed to the gendered character ( Almeling, 2011 , Tober, 2001 ) and potentially disempowering effects ( Gupta, 2006 , Pande, 2014 , Ruparelia, 2007 ) of the language of the gift, with the resulting disregard of women's labour ( Rudrappa, 2017 ). Additionally, research on surrogacy in the USA has demonstrated how gift and commodity exchange tend to overlap ( Berend, 2016 , Jacobson, 2016 , Ragoné, 1994 ), with narratives of gift-giving and relatedness facilitating commodification ( Smietana, 2017 ).…”
Section: Surrogacy As Baby-making and The Trouble Of Commodificationmentioning
confidence: 99%
“…Gendered and racialized notions of (reproductive) labour, self-sacrifice and emotion management, as well as ideological configurations of ‘choice’, are also part of the trouble, making the altruistic model of surrogacy not necessarily what it takes to avoid trouble and unhappiness (cf. Rudrappa, 2017 ).…”
Section: Conclusion: From Substitution To a Relational Being-togethermentioning
confidence: 99%
“…However, there is no consensus on the positive impact of this law. Researchers such as Rudrappa and associations such as Sama point out the perverse effect of the official wish to protect women [ 28 , 29 ], arguing that this change could promote a black market and lead to invisible coercion of women by their family and relatives (see LiveLawin , January 5, 2019). In addition, other laws have been voted in India to protect women from violence and exploitation without having a major effect on the endemic rapes, domestic violence, femicides and acid attacks [ 30 ].…”
Section: Introductionmentioning
confidence: 99%